Will Green be the Colour of Money or Life? Paradigm Wars and the Green Economy - Shiva, Vandana (Scienze del Territorio, 2014)
The green economy agenda for Rio+20 will either deepen the privatization of the Earth, and with it the crisis of ecology and poverty, or it can be used to re-embed economies within the ecology of the Earth. Green economy needs to be authentically green. To address the ecological crisis, we must stop the war against the Earth and avoid taking such crisis to deeper levels through further commodification of nature and her services as is being proposed in some versions of green economy. The latter is the old paradigm in green clothes. It has no place either for people or for Gaia’s laws. It is still driven by the flawed laws of the financial markets. We have to follow another paradigm of green economy, a paradigm that is Earth-centred and people-centred. Earth-centred green economy begins with the recognition of the rights of Mother Earth and, with this, the rights of all Earth species, including the human species. This is the path of Earth democracy, it is the path of caring and sharing. It is the path to freedom.